One year impact estimation of a workplace health promotion programme in Bergamo province - Cremaschini, Marco; Moretti, Roberto; Brembilla, Giovanni; Valoti, Marinella; Sarnataro, Francesco; Spada, Pierangelo; Mologni, Graziella; Franchin, D.; Antonioli, Lucia; Parodi, Daniela; Barbaglio, Giorgio; Masanotti, Giuseppe; et al. (La Medicina del Lavoro, 2015)
Objectives: To estimate short-term effects of integrated health promotion in the workplace within the framework of the Ber-gamo WHP (Workplace Health Promotion) network, which involves 94 companies and about 21,000 workers. Methods: A controlled non-randomized, before-after evaluation was carried out. Data were collected through anonymous questionnaires before (t0) and after participation in a 12-month health promotion programme (t1). The “control” group consisted of workers of companies participating in the programme who had not yet undertaken any interventions in the theme areas covered by the assessment. Results: In the workers participating in the programme, positive early effects (after 12 months) were related to intake of food providing protection (fruit and vegetables) and increased rates of smoking cessation. The effects were more evident in males and in white collars. The physical activity and alcohol consumption trends went in the desired direction and with more effects than in the non-participating group, but without statistical significance. In the short term, no evident changes in events of road injury risk or in the quality of personal relationships were seen, probably due to the small size of the sample involved in these study areas. Conclusions: The results, although within the methodological limitations of the study, showed that after 12 months there was a reduction in some important risk factors for chronic diseases in workers participating in the programme, particularly for fruit and vegetable intake and smoking cessation. It will be important to monitor the effects of the programme on other risk factors in the medium and long term, and also the impact of employment status and gender so as to adjust the programme interventions accordingly. Cooperation with occupational/authorized physicians with use of their data collected from health surveillance, together with a limited set of general risk factor indicators, would be a desirable development for further studies.